Polyphenol intake and cardiovascular risk factors in a population with type 2 diabetes: The TOSCA.IT study. Issue 6 (December 2017) - Vitale, Marilena; Vaccaro, Olga; Masulli, Maria; Bonora, Enzo; Del Prato, Stefano; Giorda, Carlo B.; Nicolucci, Antonio; Squatrito, Sebastiano; Auciello, Stefania; Babini, Anna C.; Bani, Laura; Buzzetti, Raffaella; et al.
Summary: Background: The role of polyphenol intake on cardiovascular risk factors is little explored, particularly in people with diabetes. Aim: To evaluate the association between the intake of total polyphenols and polyphenol classes with the major cardiovascular risk factors in a population with type 2 diabetes. Methods: Dietary habits were investigated in 2573 males and females participants of the TOSCA.IT study. The European Prospective Investigation on Cancer and Nutrition (EPIC) questionnaire was used to assess dietary habits. In all participants, among others, we assessed anthropometry, plasma lipids, blood pressure, C-reactive protein and HbA1c following a standard protocol. The USDA and Phenol-Explorer databases were used to estimate the polyphenol content of the habitual diet. Results: Average intake of polyphenols was 683.3 ± 5.8 mg/day. Flavonoids and phenolic acids were the predominant classes (47.5% and 47.4%, respectively). After adjusting for potential confounders, people with the highest intake of energy-adjusted polyphenols (upper tertile) had a more favorable cardiovascular risk factors profile as compared to people with the lowest intake (lower tertile) (BMI was 30.7 vs 29.9 kg/m 2, HDL-cholesterol was 45.1 vs 46.9 mg/dl, LDL-cholesterol was 103.2 vs 102.1 mg/dl, triglycerides were 153.4 vs 148.0 mg/dl, systolic and diastolic blood pressure were respectively 135.3 vs 134.3 and 80.5 vs 79.6 mm/Hg, HbA1c was 7.70 vs 7.67%, and C-reactive Protein was 1.29 vs 1.25 mg/dl, p < .001 for all). The findings were very similar when the analysis was conducted separately for flavonoids or phenolic acids, the two main classes of polyphenols consumed in this population. Conclusions: Polyphenol intake is associated with a more favorable cardiovascular risk factors profile, independent of major confounders. These findings support the consumption of foods and beverages rich in different classes of polyphenols particularly in people with diabetes. Clinical trial: http://www.clinicaltrials.gov ; Study ID number: NCT00700856 .